Réponses

2013-10-25T17:33:29+02:00
A = 2/3 + 7/6
   =4/6 + 7/6=11/6
B = (-1)/7+(-8)/5
   = -5/35+(-56/35)
   = -5/35-56/35=-61/35
C = -18/5-(-5)/3
   = -54/15-(-25/15)
   =-54/14+25/15=-29/15
D = -7/8+(-5)/9
   = -63/72+(-40/72)
   = -63/72-40/72=-103/72
E = 5/3+(-1)/4
   = 20/12+(-3/12)
   =20/12-3/12=17/12
2013-10-25T17:43:17+02:00
A = 2/3 + 7/6
= 4/6 + 7/6
= 11/6

B = (-1)/7 + (-8)/5
= -5/35 + (-56)/35
= -61/35

C = -18/5 - (-5)/3
= -54/5 + 25/15
= -29/15

D = (-7)/8 + (-5)/9
= -63/72 + (-40)/72
= -103/72

E = 5/3 + (-1)/4
= 20/12 + (-3)/12
= 17/12